2020
DOI: 10.1016/j.arth.2020.02.045
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bladder Catheterization on Ambulation and Venous Thromboembolism Following Total Knee Arthroplasty: An Institutional Analysis

Abstract: Background: Although intermittent catheters are immediately removed, indwelling catheterization may lead to decreased ambulation and participation in physical therapy, critical components to post-total knee arthroplasty (TKA) management. Therefore, this study aimed to compare the effect of catheterization treatments on (1) postoperative ambulation distances, (2) deep vein thromboses (DVTs), and (3) pulmonary emboli (PEs) following TKA. Methods: A total of 9123 prospectively collected primary TKA patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Additionally, less indwelling catheter time should theoretically decrease rate of postoperative urinary tract infections. Patients also ambulate less with a catheter in place, 16 , 17 which has the potential to increase the risk for postoperative deep venous thrombosis. Catheter dysfunction is also a postoperative issue, causing for patient concern and unintended emergency room visits for clogging and/or poor drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, less indwelling catheter time should theoretically decrease rate of postoperative urinary tract infections. Patients also ambulate less with a catheter in place, 16 , 17 which has the potential to increase the risk for postoperative deep venous thrombosis. Catheter dysfunction is also a postoperative issue, causing for patient concern and unintended emergency room visits for clogging and/or poor drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a notable reduction in the usage of indwelling catheters in the RRP group (39.0% versus 98.0%), which has been correlated with increased postoperative urinary traction infections, higher hospital costs, and decreased postoperative ambulation distance after TJA. 35,36 In addition, the use of closed suction drains markedly decreased in the RRP group (20.4% versus 94.5%), which has been previously correlated with a greater need for transfusion postoperatively. 37,38 To further limit blood loss and transfusion requirement, intravenous TXA was also administered TXA intraoperatively.…”
Section: Discussionmentioning
confidence: 82%
“…6 Studies involving 7,306 patients undergoing THA and 9,123 undergoing TKA evaluated the risk of postoperative UTI, postoperative mobility, and the development of POUR in patients with and without indwelling urinary catheters. 7,8 The authors concluded that postoperative UTI was significantly higher in the catheter group compared with the noncatheter group (P < .001), and if POUR developed, intermittent catheterization was favored over indwelling catheterization. 7,8 In the TKA cohort, indwelling catheterization delayed mobility and ambulation distance, and consequently increased the risk for deep vein thrombosis (DVT) (odds ratio, 2.605, P < .001), even after implementing DVT prophylaxis (odds ratio, 2.807, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…16 All of the analyses advocated eliminating the routine use of indwelling urinary catheterization, though several found no significant adverse reactions with the use of intermittent catheterization. [1][2][3][5][6][7][8][9][10][11][12][13]16 Most of the studies contended that the act of catheterization itself puts patients at risk for POUR, CAUTI, and urethral injury. 6,8,9,11,13,14 The studies cited involved 49,703 patients.…”
Section: Limitationsmentioning
confidence: 99%